TINJAUAN HUKUM TERHADAP PENGEDITAN WAJAH MENJADI MEME ATAU STIKER WHATSAPP - Sahputra, Irvan; Siregar, Tondy Danseswara (Law Jurnal, 2025)
This research uses a normative juridical research method that aims to analyze the legal implications of face editing into memes or stickers on social media, especially on the WhatsApp platform. This phenomenon has developed as a form of digital communication, but it also raises the potential for legal violations, including violations of privacy rights, insults, and copyright. Based on an analysis of relevant laws and regulations, such as the ITE Law, Copyright Law, and Criminal Code, it was found that such actions can lead to legal sanctions in the form of imprisonment or significant fines. In addition, this research also highlights the challenges of law enforcement in the digital world, which is often more complex than in the real world due to the anonymity and rapidity of information dissemination. Therefore, the study recommends preventive measures, including public education on digital ethics, strengthening social media platform policies, and intensive socialization of applicable regulations. These measures are expected to minimize the risk of law violations and create a safer and more responsible digital space.